saykaylaa2x
saykaylaa2x
17-11-2015
Mathematics
contestada
8(t+2)-3(t-4)=6(t-7)+8
Respuesta :
apologiabiology
apologiabiology
17-11-2015
PEMDAS
the first thing is multiply or distribute
a(b+c)=ab+ac
8(t+2)=8t+16
-3(t-4)=-3t+12
6(t-7)=6t-42
the equation comes out to
8t+16-3t+12=6t-42+8
add like terms
5t+28=6t-34
subtract 5t from both sides
28=t-34
add 34 to both sides
62=t
Answer Link
VER TODAS LAS RESPUESTAS ( 51+ )
Otras preguntas
The average of a list of 4 numbers is 90.0. A new list of 4 numbers has the same first 3 numbers as the original list, but the fourth number in the original lis
There are 435 representatives in the House. Suppose that 130 representatives are Democrats and 260 are Republicans; the rest are Independents. Assume that no re
A disk-shaped merry-go-round of radius 2.93 m and mass 165 kg rotates freely with an angular speed of 0.691 rev/s . A 62.4 kg person running tangential to the r
five over six divided by 2
what is the difference between linear pair and angles on a straight line
What the answer to 3(x – 1) < -3(2 – 2x)
Help me please, will give brainly
The likelihood of death within twenty years of a diagnosis for DCIS (ductal carcinoma in situ, a type of breast cancer) is only 3.3%. Does this mean that every
The value of Y varies directly with x. When y =75, x= 1/2. What is the value of y when x = 2.5?
A client who had a transurethral resection of the prostate is to be discharged from the outpatient surgical department. Which client statement indicates to the
ACCESS MORE